Quality of life assessment in perimenopausal women with abnormal uterine bleeding and endometrial hyperplasia - F. V. Abdiyeva (IRBIS LLC, 2021)
Aim: to assess the effects of several symptoms on the quality of life (QoL) in perimenopausal women with endometrial hyperplasia and abnormal uterine bleeding (АUB). Materials and Methods. This study was conducted from September, 2019 to June, 2020. In total, 50 women aged 45-55 years who visited gynecological department with complaints of AUB were randomly interviewed by using relevant questionnaire. MENQOL (Menopause-Specific Quality of Life Questionnaire) was used to assess and evaluate perimenopause related symptoms. Menopausal status was classified according to the definition of menopause proposed by the World Health Organization. Results. The majority (the total of 97.14 %) of women experienced at least five or more menopausal symptoms. Vasomotor symptoms were recorded as hot flushes (80 %), sweating (70 %), and night sweating (62 %). The most common physical symptoms were frequent back pain in the lumbar region (96 %), decreased physical strength (92 %), generalized weakness, tiredness (90 %), weight gain (80 %), and pain in the neck (90 %). Among participants, there were reported various problems such as depressive feeling of unknown reasons (20 %), anxiety and nervousness (20 %), dissatisfaction with personal life (44 %), poor memory (14 %), low mood (14 %), as well as impatience and irritability (12 %). Sexual problems were reported as changed sexual drive (20 %), vaginal dryness (10 %), and few avoided intimate contacts with the partners (10 %). Menopausal status, educational level and body mass indexes as well as marital status were also studied as those among the multi-factors significantly associated with the frequency and severity of menopause related symptoms. Conclusion. The severity of perimenopausal symptoms decreases the QoL in everyday life of women aged 45-55 years with endometrial hyperplasia and АUB.